Seasonal Variations in the Biodiversity, Ecological Strategy, and Specialization of Diatoms and Copepods in a Coastal System With Phaeocystis Blooms: The Key Role of Trait Trade-Offs - Breton, Elsa; Christaki, Urania; Sautour, Benoit; Demonio, Oscar; Skouroliakou, Dimitra-Ioli; Beaugrand, Gregory; Seuront, Laurent; Kléparski, Loïck; Poquet, Adrien; Nowaczyk, Antoine; Crouvoisier, Muriel; Ferreira, Sophie; et al. (Frontiers in Marine Science, 2021)
Although eutrophication induced by anthropogenic nutrient enrichment is a driver of shifts in community composition and eventually a threat for marine biodiversity, both the key mechanisms at work and the consequences on ecosystem functioning, remain poorly known. Here, by applying a trait-based approach and measuring niche breadth, we explored the drivers and underlying mechanisms of the seasonal species succession and biodiversity of diatoms and copepods in a coastal system marked by spring Phaeocystis blooms, a widespread Prymnesiophyte blooming in different nutrient-enriched areas worldwide. Our results showed that the seasonal succession of these plankton communities was shaped by several trade-offs among functional traits dictated by the abiotic and biotic pressure encountered by the plankton communities across the season. In particular, our results strongly suggested that a competition-predator trade-off played an important role in promoting plankton species richness and even triggering the Phaeocystis bloom. Although the Phaeocystis bloom led to biotic homogenization of the copepod community - as often observed in other eutrophicated ecosystems - no negative effect was detected on the plankton community. Our results showed that the diatom and copepod communities respond in a flexible way to varying resources and biotic conditions by favoring successively species having ecological strategies that match with environmental conditions. Altogether, the results emphasized the key role of seasonal prey-prey and prey-predator interactions.